2008
DOI: 10.1016/j.jacc.2008.02.065
|View full text |Cite
|
Sign up to set email alerts
|

Supraventricular Tachycardia After Orthotopic Cardiac Transplantation

Abstract: The majority of SVTs in stable OHT patients can be attributed to macro-reentrant tachycardias (flutter and scar reentry). Catheter ablation is effective in management of these SVTs. Atrial fibrillation was never encountered in stable patients in our series, and its occurrence should prompt an evaluation for acute rejection and/or vasculopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
146
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(155 citation statements)
references
References 34 publications
9
146
0
Order By: Relevance
“…1,2 After cardiac transplantation, atrial fibrillation (AF) or atrial flutter (AFL) are frequent in the immediate postoperative period and are associated with acute rejection or transplant vasculopathy, but macroreentrant or focal atrial tachycardia (AT) are observed later after cardiac transplantation. 3 AT and AFL observed after atrial surgery are often related to surgical lines of conduction block and regions of slow conduction. [3][4][5] AT in the recipient atria conducting to the donor atria has also been described after cardiac transplantation.…”
mentioning
confidence: 99%
“…1,2 After cardiac transplantation, atrial fibrillation (AF) or atrial flutter (AFL) are frequent in the immediate postoperative period and are associated with acute rejection or transplant vasculopathy, but macroreentrant or focal atrial tachycardia (AT) are observed later after cardiac transplantation. 3 AT and AFL observed after atrial surgery are often related to surgical lines of conduction block and regions of slow conduction. [3][4][5] AT in the recipient atria conducting to the donor atria has also been described after cardiac transplantation.…”
mentioning
confidence: 99%
“…In general, focal AT originating from the donor RA has rarely been observed, except for in cases with an atrial insult such as rejection or ischemia. 1,13) This case, however, had normal contraction and no signs of rejection including any cell-mediated immunity or humoral immunity, vasculopathy judged by coronary angiography and an intravascular ultrasound analysis, or infection.…”
Section: Discussionmentioning
confidence: 86%
“…1) Their frequency was reported to be 12% to 17% of all orthotopic heart transplantation patients studied and 2.3% in the pediatric orthotopic heart transplantation population. [2][3][4] Most of previously reported supraventricular tachycardias had a reentry mechanism involving substrates such as scars and pre-existing accessory pathways, or a dual atrioventricular nodal physiology in donor hearts.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies demonstrated that about a quarter of these patients developed SVT attributed to macro-reentrant tachycardia, and about 4% underwent EP studies [2,3]. Anesthesia for ablation procedures in these patients mandate several considerations including transplant technique used, interventional cardiology procedure performed, and particular complications common to post transplant patients.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of an increasing number of patients surviving cardiac transplantation and the relatively high incidence of atrial arrhythmias in these patients, ablation procedures under anaesthesia may be required [2,3]. Percutaneous catheter ablation is done with applying electrical triggers around the pulmonary vein ostia in order to accomplish pulmonary vein isolation using radiofrequency current.…”
Section: Introductionmentioning
confidence: 99%